KNOWLEDGE OF POLYPROPYLENE MICROPLASTICS AS A BREAST CANCER RISK FACTOR AMONG FEMALE EDUCATORS IN NILAI, MALAYSIA - Zain, Norhayati Mohd; Ridzwan, Nur Shafiqah Mohamed; Che Mut, Nur Anis Izzati (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2025)
Breast cancer remains a leading cause of mortality among women worldwide, with emerging research suggesting a potential link between environmental pollutants—such as polypropylene microplastics (PPMPs)—and increased cancer risk. Despite growing concern, public awareness regarding PPMPs as a possible risk factor for breast cancer remains poorly understood, particularly among women in influential educational roles. This study aimed to assess the level of knowledge regarding PPMPs as a breast cancer risk factor among female educators and to examine associations between knowledge levels and demographic variables. A cross-sectional study was conducted among 151 female educators across multiple schools in Nilai, Malaysia, using a self-administered, validated bilingual questionnaire. Data were collected both in-person and online via convenience and snowball sampling. Descriptive and inferential statistics (chi-square test) were used to analyse the relationship between knowledge levels and variables such as age, education, marital status, household income, and health history. Over half of the respondents (52.3%) demonstrated poor knowledge of PPMPs as a breast cancer risk factor. While 72.2% were aware of a possible health risk, only 36.4% correctly identified the inflammatory mechanism associated with PPMP exposure. Significant variability in knowledge was observed across age, race, and income groups. Social media was the most common source of information, while formal education was the least common. The findings show a major lack of awareness and understanding of environmental breast cancer risk factors among educators, highlighting the need for focused education and public health efforts to raise environmental health literacy and support cancer prevention.